An effective cell-based smoothed finite element model for the transient responses of magneto-electro-elastic structures. (August 2018) - Zhou, Liming; Li, Ming; Meng, Guangwei; Zhao, Hongwei
To overcome the over-stiffness and the imprecise magneto-electro-elastic coupling effects of finite element model, we presented a cell-based smoothed finite element model to more accurately simulate the transient responses of magneto-electro-elastic structures. In the cell-based smoothed finite element model, the gradient smoothing technique was introduced into a magneto-electro-elastic multi-physical-field finite element model. The cell-based smoothed finite element model can achieve a close-to-exact stiffness of the continuum structures which could automatically discrete elements for complicated regions more readily and thus remarkably reduced the numerical errors. In addition, the modified Wilson- θ method was presented for solving the motion equation of magneto-electro-elastic structures. Several numerical examples were investigated and exhibited that the cell-based smoothed finite element model could receive more accurate and reliable simulation results than the standard finite element model. Besides, the cell-based smoothed finite element model was employed to calculate transient responses of magneto-electro-elastic sensor and typical micro-electro-mechanical systems–based magneto-electro-elastic energy harvester. Therefore, the cell-based smoothed finite element model can be adopted to tackle the practical magneto-electro-elastic problems such as smart vibration transducers, magnetic field sensors, and energy harvester devices in intelligent magneto-electro-elastic structures systems.